GEOLOGY OF THE APTIAN-ALBIAN COGOLLO GROUP CARBONATE PLATFORM AND IMPLICATIONS WITH THE OCEANIC ANOXIC EVENTS, MARACAIBO BASIN, NORTHWESTERN SOUTH AMERICA - Aura S. García (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The relevance of the research is caused by the need of driving boost a detailed and updated re-exploration process that allows not only predicting with accuracy the behavior of currently producing fields, but also expanding new possibilities for localization and development of oilfields resource in the Maracaibo basin of western Venezuela. The Cogollo group, represented by the Apón, Lisure and Maraca formations, constitutes a very important interval since it contains the main carbonate deposits and source rocks of the Cretaceous in the west of Venezuela. The levels of source rock correspond to the oceanic anoxic events 1a y 1b. The first event corresponds to Machiques Member, and the second one is located near the top of the Piché Member, both belonging to the Apón formation. As these events generated deposits with high potential as hydrocarbon source rocks, remain a major subject of interest and research. The main aim of the research is to recognize facies of the deposit and the correlation with adjacent wells, for location of reservoir units and their possible association with potential intervals of source rock of the Lower Cretaceous in the territory of Maracaibo basin, Venezuela. The research objects are outcrop sections of the quarry in Cementos Catatumbo C.A of Perijá Range, where the Lower Cogollo group carbonate succession and oil wells X-1, X-15, X-21, X-14 and X-23 are presented. Correlation analyses that include outcrops information at Perija Range are insufficiently justified and need to be clarified. Research methods: sedimentological analysis of the carbonate rocks of the Cogollo Group, through the analysis of a section of surface in the quarry of Cementos Catatumbo C.A of Zulia state, Venezuela, integrating sedimentary, biostratigraphic, total organic carbon and Gamma-Ray data. Results. The author has identified 14 microfacies associated with a scenario of a carbonate ramp basin. In the succession of rocks of the Apón Formation a maximum flooding surface and a drowning unconformity are distinguished. An approximated and estimated correlation taking into account stratigraphy, lithofacies and the GR responses was carried out with the outcrop section of quarry in Cementos Catatumbo C.A and oil wells X-1, X-15, X-21, X-14 and X-23.